Diarrhoeagenic Escherichia coli in mother-child Pairs in Ile-Ife, South Western Nigeria. Issue 1 (December 2015) - Odetoyin, Babatunde; Hofmann, Jennifer; Aboderin, Aaron; Okeke, Iruka
Abstract Background DiarrhoeagenicEscherichia coli (DEC) pathotypes are among the most common bacterial causes of morbidity and mortality in young children. These pathogens are not sought routinely and capacity for their detection is limited in Africa. We investigated the distribution and dissemination of DEC in 126 children paired with their mothers in a Nigerian community. Methods A total of 861E. coli were isolated from 126 children with diarrhoea and their mothers. Antimicrobial susceptibility of each isolate was determined by Kirby-Bauer disc diffusion technique. All the isolates were screened for DEC markers by multiplex PCR. Genetic relatedness of DEC strains was determined by flagellin typing and Insertion element 3 (IS3 )-based PCR. Results DEC were identified from 35.7 % of individuals with the most common pathotype being shiga toxin-producingE. coli (42, 16.7 %). Identical pathotypes were found in 13 (10.3 %) of the mother-child pairs and in three of these strains from mothers and their children showed identical genetic signatures. Over 90 % of DEC isolates were resistant to ampicillin, sulphonamide, tetracycline, streptomycin or trimethoprim, but only 9 (7.2 %) were ciprofloxacin resistant Conclusion The data suggest that healthy mothers are asymptomatic reservoirs of multiply-resistant strains that are pathogenic in their children and there are instances in which identical strains are found in mother-child pairs.